Zastrupitev z etilenglikolom - Hojs, Nina (Medicinski razgledi, 2011)
Ethylene glycol intoxications are quite rare. The toxicity of ethylene glycol is largerly related to its metabolites rather than the parent compound itself. Our case report represents the typical clinical findings (neurological, cardiopulmonary and renal phase) and laboratory results (elevated serum osmolality, high osmolar gap, high anion gap metabolic acidosis, calcium oxalate crystals in the urine) of an glycol intoxication. Given the potentially high morbidity and mortality of this intoxication, its quick recognition is essential. Treatment includes securing the patient's airway, breathing and circulation, administering bicarbonate and an antidote (ethanol, fomepizole), hemodialysis, and sometimes also the administration of cofactors of ethylene glycol metabolism (thiamine, pyridoxine, and magnesium).
Keywords: Ethylene Glycol; Etilenglikol; poisoning; Zastrupitve; Zdravljenje; diagnosis; Nujno ukrepanje; therapy; Osmolarna koncentracija; Diagnostika; Emergency Treatment; Acido-bazno ravnotežje; Osmolar Concentration; klinična slika; Acid-Base Equilibrium